Modelling and Virtual Manufacturing of a Flange Tube Using CAD/CAM Tools - Ibrahim, Musa Alhaji; Shuaibu Ahmad, Abdulrahman; Gidado, Auwalu Yusuf; Abubakar, Saidu Bello; Kai, Huang (Journal of Advanced Research in Applied Mechanics, 2020)
Virtual manufacturing, as an advanced machining technology, has been regarded as a useful tool to carry out analysis and research work with digital model instead of practical manufacture. In virtual manufacturing, there is no real production and neither material nor power is wasted. Modelling, mould design, assembly and virtual manufacture of a flange tube has been carried out through the application of such automation technology as CAD/CAM. A CAD tool, Pro/Engineer Wildfire 4.0 software package was used in the modelling of a flange tube as well as in the design and assembly of the mould for the created part. These were achieved based on the dimensions and specifications of both the blank and the finished drawings. The 3D solid model was imported in IGES format from the Pro/Engineer into a CAM tool, MasterCAM4.0 for the virtual manufacture of the flange tube through NC machining simulation of the wax pattern injection mould cavity. The results showed that the part can be modelled and manufactured virtually using CAD/CAM tools and this reduces cost of real prototype, increases performance, improve on product quality and shortens production development cycle.